A novel electro‐thermal coupled model of lithium‐ion pouch battery covering heat generation distribution and tab thermal behaviours. (24th August 2020) - Xie, Yi; He, Xiaojing; Li, Wei; Zhang, Yangjun; Dan, Dan; Lee, Kuining; Liu, Jiangyan
Summary: This paper develops an electro‐thermal coupled model for a pouch battery which considers the influence of the electric potential distribution and thermal behaviours of tabs on the distributions of heat generation and temperature. This model reflects the connection between electric potential distribution and the heat generation distribution. Then, the proposed electro‐thermal model is used to predict the thermal behaviour of a lithium‐ion pouch battery under the conditions of various discharge currents and environmental temperatures. Tests are implemented to verify the prediction precision of the proposed thermal model. The results show that the electro‐thermal coupled model can accurately predict both the temperature distribution and its rise. At 1 C discharge rate, the average mean static absolute errors (MSAEs) in the positive and negative tabs for all the ambient temperatures are 1.083 K and 0.377 K, respectively, and the average MSAE in the battery body is only 0.627 K; at the discharge rate of 3.5 C, the respective average MSAEs are 1.643 K for the positive tab, 0.581 K for the negative tab, and 0.889 K for the battery body. Last, the influence of the thermal contact resistance on the prediction of the tab temperature is studied. If it is considered in the thermal model of tabs, the predicted tab temperature is closer to the tested value and the MSAE can be limited within 2.65 K for the positive tab and 0.83 K for the negative tab in the cases researched.